2019–2020 Florida Citrus Production Guide: Quick Reference Guide to the Worker Protection Standard (WPS) - Frederick Fishel (EDIS)
The Worker Protection Standard (WPS) is a regulation originally issued by the US Environmental Protection Agency (EPA) in 1992 and most recently revised in 2015. This regulation is primarily intended to reduce the risks of illness or injury to workers and pesticide handlers resulting from occupational exposures to pesticides used in the production of agricultural plants on agricultural establishments (i.e., farms, forests, nurseries, and enclosed-space production facilities such as greenhouses). This 8-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Frederick M. Fishel and published by the Entomology and Nematology Department, March 2019.